Diabetogenic liver metastasis from pancreatic cancer: a case report - Sho Kiritani; Yoshihiro Ono; Manabu Takamatsu; Atsushi Oba; Takafumi Sato; Hiromichi Ito; Yosuke Inoue; Yu Takahashi (Surgical Case Reports, 2022)
Abstract Background Although new-onset diabetes has been described in up to 20% of patients with newly diagnosed pancreatic cancer, reports regarding new-onset diabetes associated with newly developed liver metastasis from pancreatic cancer are limited. Case presentation A 60-year-old man was diagnosed with pancreatic tail cancer without impaired glycemic control. A curative-intent distal pancreatectomy with adjuvant S-1 chemotherapy was performed. Two years after surgery, a high HbA1c concentration and solitary liver metastasis were identified on follow-up examination. Two major chemotherapy regimens, gemcitabine/nab-paclitaxel and modified FOLFIRINOX, were sequentially administered to the patient; however, his carbohydrate 19-9 concentration continued to increase. Because the patient’s glycemic control rapidly worsened in synchrony with the tumor growth, insulin therapy was initiated. Although the liver metastasis was refractory to chemotherapy, curative-intent left hepatectomy was performed because only one tumor remained. His impaired glycemic control improved immediately after surgery, and insulin therapy was terminated. When writing this report (2 years after hepatectomy), the patient was alive and recurrence-free. Conclusions New-onset diabetes appeared with the progression of metachronous liver metastasis from pancreatic cancer, without recurrence at any other site. The patient’s diabetic state was improved by resection of the liver tumor, and liver metastasis itself was proven to have caused the glucometabolic disorder by increasing insulin resistance.